2013
DOI: 10.1037/a0030599
|View full text |Cite
|
Sign up to set email alerts
|

Contextual control of attentional allocation in human discrimination learning.

Abstract: In 3 human predictive learning experiments, we investigated whether the allocation of attention can come under the control of contextual stimuli. In each experiment, participants initially received a conditional discrimination for which one set of cues was trained as relevant in Context 1 and irrelevant in Context 2, and another set was relevant in Context 2 and irrelevant in Context 1. For Experiments 1 and 2, we observed that a second discrimination based on cues that had previously been trained as relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…Uengoer, Lachnit, Lotz, Koenig, and Pearce (2013) and George and Kruschke (2012) demonstrated that changes in associability can come under the control of contextual stimuli.…”
Section: Context Modulation Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…Uengoer, Lachnit, Lotz, Koenig, and Pearce (2013) and George and Kruschke (2012) demonstrated that changes in associability can come under the control of contextual stimuli.…”
Section: Context Modulation Ofmentioning
confidence: 99%
“…One aim was to assess the validity of the conclusion in terms of context-specific attention drawn from the studies by Uengoer et al (2013) and George and Kruschke (2012). In these two previous studies, contextual control of attention during initial training was inferred from subsequent differences in learning rates.…”
Section: Context Modulation Ofmentioning
confidence: 99%
See 3 more Smart Citations